Strategi Pelestarian Aksara Sasak melalui Mobile Game Edukatif Berbasis ADDIE - Anas, Andi Sofyan; Tajuddin, Muhammad; Adil, Ahmat; Hammad, Rifqi (Institut Teknologi Adhi Tama Surabaya, 2025)
The Sasak script is an essential part of the cultural identity of the Sasak people in Lombok. However, interest among the younger generation in learning this script has been declining due to the dominance of the Indonesian language and globalization. Therefore, innovation in learning methods is necessary to ensure that the Sasak script remains preserved and appealing to students. One potential approach is gamification through educational mobile games. This study aims to develop a mobile game as a learning medium for the Sasak script using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. In the analysis phase, user needs and challenges in learning the Sasak script are identified. The design phase involves creating engaging gamification elements and an intuitive user interface. The development phase focuses on implementing technology to develop the mobile game. The game is then tested during the implementation phase, followed by the evaluation phase, which assesses its effectiveness in increasing students’ interest and understanding of the Sasak script, as well as evaluating the game’s content and interface. The results show that an ADDIE-based mobile game can enhance students’ motivation to learn the Sasak script. The use of gamification effectively creates a more interactive and enjoyable learning experience. Thus, this study contributes to the preservation of the Sasak script while providing an innovative solution for regional language education through digital technology.